EXPERIMENTS IN SQUARE LATTICE WITH A COMMON TREATMENT IN ALL BLOCKS - Pimentel Gomes, F.; Viegas, Glauco P. (REVISTA DE AGRICULTURA, 2020)
EXPERIMENTS IN SQUARE LATTICE WITH A COMMON TREATMENT IN ALL BLOCKS